Recommended values of thermophysical properties for selected commercial alloys - Mills, K. C. (Woodhead, 2002)
The work contained in this report was carried out as part of the National Physical Laboratory's MTS Programme on Processability, the purpose of which was to provide engineers with the best possible data on commercially available alloys to help with the mathematical modelling of processes such as casting and refining. Mathematical modelling has become an increasingly useful tool in improving process control and efficiency and product quality. Models have been developed to the stage where one of the prime requirements is for accurate and reliable data for the thermophysical properties involved in the heating and fluid flow processes. There is very little available data in the standard literature on commercial alloys so this report fulfills a real need for all those involved in modelling processes with commercially available alloys by providing valuable data relating to:Fraction solidMelting rangeHeat capacityEnthalpyThermal diffusivity and conductivityEmissivity densityViscositySurface tensionThe book also provides a model for assessing the properties of alloys not covered individually in the work by reference to their chemical composition. Recommended values of thermophysical properties for selected commercial alloys is an important new data source for all metals refiners, metallurgists, materials scientists and engineers needing to understand the thermophysical properties of alloys for casting, primary or secondary refining.